2014
DOI: 10.1371/journal.pone.0084918
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Correlates of Serum L-Ergothioneine Concentrations in Community-Dwelling Middle-Aged and Older Adults

Abstract: BackgroundDespite the increasing interest towards the biological role of L-ergothioneine, little is known about the serum concentrations of this unusual aminothiol in older adults. We addressed this issue in a representative sample of community-dwelling middle-aged and older adults.MethodsBody mass index, estimated glomerular filtration rate, serum concentrations of L-ergothioneine, taurine, homocysteine, cysteine, glutathione, cysteinylglycine, and glutamylcysteine were evaluated in 439 subjects (age 55–85 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…It has been hypothesized that ergothioneine administration may prevent tissues against oxidative damage [71] and that decreased blood plasma levels of ergothioneine have been reported in elderly [72] and Parkinson's disease [73]. Studies in animals and humans have found no toxicity, and ergothioneine has been recently approved as a nutritional supplement [74,75].…”
Section: Ergothioneinementioning
confidence: 99%
“…It has been hypothesized that ergothioneine administration may prevent tissues against oxidative damage [71] and that decreased blood plasma levels of ergothioneine have been reported in elderly [72] and Parkinson's disease [73]. Studies in animals and humans have found no toxicity, and ergothioneine has been recently approved as a nutritional supplement [74,75].…”
Section: Ergothioneinementioning
confidence: 99%
“…Indeed, low blood plasma concentrations of ET are associated with age-related disorders [ 60 , 64 , 74 ], suggesting that ET may be beneficial as a therapeutic or prophylactic supplement to reduce the risk of these disorders. Furthermore, we and others have identified that blood ET levels decline with advancing age, possibly predisposing elderly individuals to an increased risk of age-related disorders [ 60 , 72 , 75 ], which may include frailty, cardiovascular disorders, and neurodegenerative disease.…”
Section: Biology Of Ergothioneinementioning
confidence: 99%
“…61 One of them is the ability to scavenge free radicals, which can be proposed to arise from the easy one-electron oxidation of its mercapto group to a disulfide, similarly to the main water-soluble antioxidant thiol glutathione. 62 However, ERT chemistry differs from conventional sulfur-containing antioxidants mainly because it exists as a tautomer between its thiol and thione forms, with the latter predominating under physiological conditions.…”
Section: Ergothioneinementioning
confidence: 99%